Berbagi Ruang Omotenashi berdasarkan Aspek Kekeluargaan dan Kehangatan di Kawasan Jam Gadang Bukittinggi - Imma Widyawati Agustin; Fanny Safitri; Septiana Hariyani (I-Com: Indonesian Community Journal, 2025)
The increasing number of private vehicles is directly proportional to the density of traffic which then causes the transportation system to be focused on widening roads or providing infrastructure to meet the increasing volume of vehicles. On the other hand, adding roads or widening lanes is not considered effective in organizing the transportation system because widening the road will only increase the number of vehicles traveling instead of reducing. This research aims to develop a space sharing design that can be applied to the Jam Gadang area. The analysis used is Quality Deployment Analysis (QFD) and 6 stages of analysis in sharing space. The final results showed that the space sharing design chosen by pedestrians was a road and sidewalk model with paving pavement and without a barrier between pedestrians and vehicle users, while vehicle users chose a space sharing design with road pavement using asphalt and sidewalk pavement using paving.